The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31557/apjcp.2020.21.4.867
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Epidemiology of Breast Cancer in Asia: Focus on Risk Factors

Abstract: Background and Aim: Breast cancer is the most prevalent cancer in women. To date, regional differences in breast cancer risk factors have not been identified. The aim of our review was to gain a better understanding of the role of risk factors in women with breast cancer in Asia. Methods: We conducted a PubMed search on 15 March 2016, for journal articles published in English between 2011 and 2016, which reported data for human subjects in Asia with a diagnosis of breast cancer. Search terms included breast ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
69
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 128 publications
1
69
0
5
Order By: Relevance
“…Although advances have been achieved in the prevention and treatment of breast cancer in recent decades, the disease remains one of the most common malignancies in women ( 1 , 2 ). It has been reported that ~1.4 million women are diagnosed as breast cancer each year all over the world, and breast cancer remains an important cause of mortality in women ( 3 , 4 ). The 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase inhibitors, also known as statins, are the most commonly use lipid-lowering medications which have become a cornerstone for the prevention and treatment of atherosclerotic cardiovascular diseases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although advances have been achieved in the prevention and treatment of breast cancer in recent decades, the disease remains one of the most common malignancies in women ( 1 , 2 ). It has been reported that ~1.4 million women are diagnosed as breast cancer each year all over the world, and breast cancer remains an important cause of mortality in women ( 3 , 4 ). The 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase inhibitors, also known as statins, are the most commonly use lipid-lowering medications which have become a cornerstone for the prevention and treatment of atherosclerotic cardiovascular diseases ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Its morbidity and mortality are rising sharply in this decade. 2 In addition, with the development of modern diagnostic methods, more and more studies started focusing on the non-invasive diagnostic molecular biomarkers such as microRNAs which contributed to the metastasis of breast cancer. 3 However, the survival rate of patients carrying metastatic breast cancer has dramatically increased in recent years due to a variety of intrinsic and extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%
“… 3 However, the survival rate of patients carrying metastatic breast cancer has dramatically increased in recent years due to a variety of intrinsic and extrinsic factors. 2 Besides that, the proliferation ability and highly activated cell cycle are the crucial factors contributing to metastasis of different cancers. 4 Therefore, to find the effective diagnostic and treatment method of breast cancer, there is an urgent requirement for a clearer understanding of the mechanisms associated with metastatic breast cancer at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common type of cancer and the leading cause of cancer death in women worldwide (1).With 1.7 million new cases per year, it accounts for 25% of all cancers in women (2).…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic breast cancer, also known as advanced or stage IV breast cancer, can spread to other organs in the body, such as bone, liver, lung and brain, thus early detection of the disease can lead to best improved prognosis and long-term survival of breast cancer patients (13). A number of factors, including premature menstruation, late-onset menopause, late age at rst birth, breastfeeding period, socioeconomic status, smoking, low physical activity, obesity, and highfat diet have been associated with increased risk of breast cancer (2,14).…”
Section: Introductionmentioning
confidence: 99%